Neuroleukemia: a clinical case - G. A. Kharchenko; O. G. Kimirilova (Лечащий Врач, 2021)
Affection of the nervous system in acute leukemia is characterized by polymorphism of clinical symptoms, in which connection patients can seek medical help from doctors of various specializations. Eventually, this may affect the timeliness of diagnosis, treatment, and disease outcomes. The report provides a clinical observation of incomplete neuroleukemia syndrome (absence of pathological abnormalities in the cerebrospinal fluid in the presence of clinical manifestations) in a patient with acute development of lymphoblastic leukemia, which accompanied by a lesion of the facial nerve nucleus. Neuroleukemia is one of the serious complications of acute leukemia. The reason for the development of neuroleukemia is the metastasis of leukemia cells in the arachnoid and pia mater of the brain and spinal cord with the penetration of the medulla along the vessels and the formation of perivascular infiltrates, as a result of which a meningitis clinic develops with changes in the cerebrospinal fluid. The basis for the treatment of neuroleukemia is the intrathecal use of cytostatic drugs (methotrexate dexamethasone, cytarabine); intravenous administration of vincristine, cyclophosphamide, doxorubicin, daunorubicin, etc. The features of the given clinical observation is the development of neuroleukemia as the primary manifestation of acute leukemia, more often this occurs during relapse. In our observation, a patient with acute leukemia had a unilateral lesion of the facial nerve, with clinical symptoms corresponding to damage to the nucleus of the facial nerve and there were no changes in the cerebrospinal fluid, which is possible with the development with incomplete neuroleukemia syndrome of a patient. Upon achieving clinical and laboratory remission in neurological status, the patient retained paralysis of the muscles of the face on the left. The presence in patients of pallor of the skin, hemorrhagic syndrome, lymphadenopathy, hepatosplenomegaly should necessarily alert the doctor and requires the exclusion of malignant diseases of the blood system.